Neurological Characteristics Of Children With Autism (Eurasian Medical Research Periodical, 2023)
Autism is a disorder of mental and psychological development, in which there is a pronounced deficit of emotional manifestations and the sphere of communication. In translation, the word "autism" means - a person who has gone into himself, or a person inside himself. A person suffering from such a disease does not show his emotions, gestures and speech to others, and in his actions, often, there is no social meaning. This article examines the neurological characteristics of children with autism